Семья и школа формируют человека - Байдельдинова Галина Константиновна (Мектеп, 1984)
Экземпляры: КХ (20120604) / Инвентарный номер: 0267588 / Цена: 0.10 / Сис.шифр: 371.018 / Авт.знак: Б 18 / ГРНТИ: 14 / ББК: 74